SYSTEMIC LEVELS OF BIOCHEMICAL COMPONENTS AND INFLAMMATORY MARKERS IN PATIENTS WITH SEVERE OBESITY: A LITERATURE REVIEW (CIPEEX, 2025)
Introduction: Obesity is currently one of the most serious public health problems. Its prevalence has been growing sharply in recent decades, even in developing countries, turning it into a global epidemic. Severe obesity is a complex condition that manifests itself through significant changes in the systemic levels of these inflammatory markers and biochemical components, often leading to the recommendation of bariatric surgery.  Objective: To verify the systemic levels of biochemical components and inflammatory markers in different studies with the severely obese population. Methodology: Five original articles were extracted from the PubMed, Google Scholar, and Scielo databases, published between 2018 and 2024. The Health Sciences Descriptors (DeCS) used for the search were: “severe obesity,” “bariatric surgery,” and “biochemical markers,” with the Boolean operator “AND.” The inclusion criteria were publications in any language, original studies, and free access. Results: in obese individuals, there is an increase in glucose levels, blood lipids, and inflammatory markers, such as CRP and IL-6, in addition to an increase in oxidative stress, which can contribute to metabolic and cardiovascular comorbidities, requiring therapeutic interventions that modulate these markers. Conclusion: The studies analyzed demonstrated that obesity significantly impacts several biochemical markers, exacerbating both glycemic and lipid conditions and promoting a chronic inflammatory state.
Keywords: Severe obesity; Bariatric surgery; Biochemical markers